Iteration n * F (n - 1) + ((n - 1) * F (n - 2))
I am stuck with this:, n * F(n - 1)+((n - 1) * F(n - 2))
I know how to write this recursively. But don't know about iteration.
I use this for recursion:
long F_r(int n)
{
if (n <= 2)
{
return 1;
}
else if (n > 2)
{
return n * F_r(n - 1) + ((n - 1) * F_r(n - 2));
}
}
Can someone help me please?
source to share
With an array to store all intermediate F values:
long F_r(int n)
{
long[] f = new long [n + 1]; // f[0] is not used
f[1] = 1;
f[2] = 1;
for (int i = 3; i <= n; i++)
{
f[i] = i * f[i - 1] + ((i - 1) * f[i - 2]); // the formula goes here
}
return f[n];
}
If you only want to use O (1) space, please note that you do not need to store the entire array, but only the previous two values ββat a time. So this can be rewritten as in fgb's answer .
source to share
Knowing that iteration is just being debugged for n = 3
or some other values ββ(more than 3 will help better). For a mathematical understanding, whatch this:
.
.
.
F(0) = 1;
F(1) = 1;
F(2) = 1;
F(3) = 3* F(2) + (2* F(1));
= 3*1 + (2*1);
= 3 + 2;
= 5;
F(4) = 4* F(3) + (3* F(2));
= 4*5 + (3*1);
= 20 + 3;
= 23;
Etc.
source to share
Just for fun - solving the recurrence relation with Wolfram Alpha gives:
F(n) = (2 * factorial(n + 2) - 5 * subfactorial(n + 2)) / (n + 1)
What can we calculate as:
long F(int n) {
long p = 1;
long q = 1;
for (int i = 1; i <= n + 2; i++) {
p *= i;
q = q * i + (1 - (i % 2) * 2);
}
return (2 * p - 5 * q) / (n + 1);
}
source to share